The influence of serve on the organisation of the block in high-level volleyball across genders - Polychronopoulos, G.; Lamprogeorgou, M.; Drikos, S.; Gortsila, E.; Sotiropoulos, K.; Barzouka, K. (Journal of Physical Education and Sport, 2025)
This study aimed to investigate the influence of serve characteristics (type, zone, and direction) on block organisation (single, double, triple, open double, no block) in high-level volleyball, and to explore potential gender-based differences in these tactical interactions. The study sample comprised 32 games (16 male, 16 female) from the World Championships 2022. A total of 4,289 serves were analysed, using a six-level (0-5) tactical rating scale. Intra and inter-rater reliability were assessed using Cohen's K Index, which showed high consistency (>0.8). The chi-square test and Fisher's exact test were used to analyse the independence of categorical variables, with statistical significance set at p < 0.05. The results of the study indicated that the most common block type for both genders was the double block. Male athletes executed single, double, and triple blocks more frequently, predominantly using the powerful jump serve (PJS) from serving areas SA1 and SA6, while directing it primarily toward the centre of the court (CM). Female athletes performed double and open double blocks more frequently, using the float jump serve (FJS) from SA1 and SA5, directing them toward the areas near the baseline or the sidelines. Women performed double blocks more frequently, irrespective of the athletes` in-game role. In contrast, when male outside hitters and opposites served, their teams formed triple blocks more frequently than women. Following serves from middle blockers and setters, men primarily performed single and triple blocks. Males used PJSs to disrupt the opposing attack, leading to triple, single, or no blocks. In conclusion, post-serve blocking strategies displayed a clear gender-based difference, while serve type emerged as a key factor influencing block organisation.